Risk Factors and Demographic Profile of Suspected Leptospirosis Cases in Kendary City: Health Challenges in Flood-Prone Areas - Agung Mirasa, Yudied; Ahzan, Nuralim; Maria Oda, Yustina; Alifsya Ramadhani, Zhuria; Nurika, Globila; Sahri, Moch. (State Islamic University of Sunan Ampel, 2025)
Leptospirosis is a disease caused by infection with Leptospira bacteria and is commonly found in tropical and subtropical regions, such as Indonesia. This study aimed to describe the demographic data, symptoms, and risk factors of suspected leptospirosis cases in Kendari Barat and Baruga Subdistricts, Kendari City, Southeast Sulawesi Province. Data were collected from epidemiological investigation reports from Benu-benua, Lepo-lepo, and Kandai Community Health Centers. Based on the data from suspected leptospirosis cases in Kendari City, most cases were found in females (60.6%), within the productive age group (66.7%), living in flood-prone areas (51.5%), and with the presence of rats inside the home (69.7%). Living in flood-prone areas and the presence of rats in the home were prominent risk factors among suspected leptospirosis cases. It was recommended that people of working age in Kendari City use personal protective equipment when working in environments with a high risk of transmission. Additionally, personal and household hygiene should be maintained, especially during floods and in the presence of rats, as these conditions increased the risk of leptospirosis transmission.